Digital Design and Computer Architecture - Harris, David Money; Harris, Sarah L. (San Francisco, Calif. : Morgan Kaufmann ; Oxford : Elsevier Science [distributor], 2012)
'Digital Design and Computer Architecture' begins with a modern approach by rigorously covering the fundamentals of digital logic design using a hardware design language (HDL).
Previous ed.: 2007.
Includes bibliographical references and index.
Keywords: Logic design -- Data processing; Computer architecture; Computer organization; Computers and IT